Late phonological development in Williams syndrome - Pérez, Vanesa; Martínez, Verónica; Diez-Itza, Eliseo (Frontiers in Psychology, 2022)
Williams syndrome is a neurodevelopmental genetic disorder characterized by a unique phenotype, including mild to moderate intellectual disability and an uneven neuropsychological profile of relative strengths and weaknesses. Language structure components (i.e., phonology, morphosyntax, and vocabulary) have been considered an area of specific ability compared to pragmatic language use. However, research on phonological development in Williams syndrome is very scarce, and it suggests atypical patterns. Therefore, the aim of the present study was to explore the profiles of late phonological development in Spanish-speaking children, adolescents, and adults with Williams syndrome, based on the analysis of five classes of processes (Syllable Structure, Substitution, Omission, Assimilation, and Addition) in spontaneous speech. The phonological profiles of seven children (aged 3 to 8 years), and seven adolescents and young adults (aged 14 to 25 years) with Williams syndrome were compared with two normative groups of typically developing children at different stages of late phonological development (aged 3 years and 5 years). The frequency of phonological processes in the group of children with Williams syndrome was similar to that of 3-year-old typically developing children, which suggests that they would be in the first stage of late phonological development (expansion stage). The group of older individuals with Williams syndrome showed a much lower frequency of processes, similar to that of 5-year-old typically developing children in the last stage of phonological development (resolution stage). However, their phonological processes appeared to be persistent and independent of chronological age. Furthermore, asynchronies in quantitative and qualitative profiles (relative frequency) indicated atypical and complex trajectories in late phonological development, which cannot be described as simply delayed or protracted. Remarkable individual differences were observed, especially in the group of adolescents and adults with Williams syndrome, although the majority of cases conformed to the modal profiles of their groups. A major tendency for Omission, including final consonant deletion, may be considered atypical and specific to Williams syndrome at all ages. The results of the present study raise the need for continued and appropriate phonological assessment and treatment for people with Williams syndrome across the lifespan.